Assessment of the characteristic of nutrients, total metals, and fecal coliform in Sibu Laut River, Sarawak, Malaysia - Soon, C.L; Ling, Teck Yee; Nyanti, L.; Kasing, Apun (Springer, 2016)
The concentrations of nutrients (nitrogen and phosphorus), total metals, and fecal coliform (FC) coupling with chlorophyll-a (chl-a), 5-day biochemical oxygen demand (BOD5) and other general environmental parameters were evaluated at the sub-surface and near-bottom water columns of 13 stations in the Sibu Laut River during low and high slack waters. The results indicated that inorganic nitrogen (mainly nitrate) was the primary form of nitrogen whereas organic phosphorus was the major form of phosphorus. The abundance of total heavy metals in Sibu Laut River and its tributaries was in the order of Pb\Cu\Zn\Cd. Fecal coliform concentration was relatively low along Sibu Laut River. The shrimp farm effluents contributed a substantial amount of chl-a, BOD5, nutrients, and FC to the receiving creek except for total metals. Nevertheless, the influence was merely noticeable in the intake creek and amended rapidly along Selang Sibu River and brought minimal effects on the Sibu Laut River. Besides, the domestic sewage effluents from villages nearby also contributed a substantial amount of pollutants.